Experimental analysis of the tensile property of FFF-printed elastomers. (October 2020) - Lin, Xiang; Coates, Phil; Hebda, Michael; Wang, Runguo; Lu, Yonglai; Zhang, Liqun
Abstract: Designing and manufacturing functional parts with enhanced mechanical property is a major goal of fused filament fabrication (FFF) for polymeric elastomers, which exhibits major advantages in producing such parts with a range of structures. But the unsatisfactory mechanical performance constrains greatly its real application and there is yet no consensus in the mechanical characterization of printed samples. This work takes the nozzle height as the considered factor and tests the tensile property of FFF-printed thermoplastic polyurethane (TPU). Rheological property of the TPU melt, represented here by die swell behavior and shear viscosity, were measured initially to obtain a preliminary assessment of the material suitability and an optimization of melt extrusion conditions for FFF processing. Then correlation between the cross-section profile of deposited bead and the tensile performance of printed sample were evaluated. Both the shape of deposited bead and the bonding strength of two adjacent beads are emphasized when explaining the measured tensile strength. The significance of molecular permeation efficiency at bead-bead interfaces, and bonding-releasing patterns between adjacent beads to the tensile failure of printed objects is discussed. Highlights: The effect of nozzle height on tensile properties of FFF printed TPU part was explored based on the evolution of bead profile and molecule diffusion. Rheological analysis provided an initial assessment of material suitability for FFF processing. Temperature difference was found between the set and measured values. An insight of tensile property dependence was obtained through two bonded adjacent beads with three contacting models.